THE ROLE OF THE FAMILY INSTITUTION IN THE SPIRITUAL ENVIRONMENT OF SOCIETY (Scientific journal of the Fergana State University, 2025)
This article examines the role and significance of the family institution in the spiritual environment of society. The family is regarded as a key social institution responsible for shaping and transmitting spiritual values across generations. The article analyzes the impact of the family environment on the moral standards and spiritual development of society, offering recommendations to address challenges faced by families in the context of modern changes.